Implementacija GDPR v CERP-u - primer dobre prakse na Hrvaškem - Molnar, Branka (Moderna arhivistika, 2019)
The article describes the procedures for managing personal data carried out in the CERP, a legal entity with public authority, with the aim of harmonizing the provisions of the GDPR after the Law on the Implementation of the General Data Protection Regulation entered into force in the Republic of Croatia. It is emphasized that CERP is obliged to adopt the principle of publicity when it comes to data relating to its primary activity, i. e. the management of state property, but it isobliged to respect the GDPR and other regulations of the Republic of Croatia in the procedures in which the personal data of its employees or clients are listed. It introduces new types of records and documents that accompany the implementation proceduresand, together with the Special Census Materials List, determine their storage times.
Keywords: CERP; GDPR; implementacija; implementation; odprti podatki; open data; osebni podatki; personal data